T Cells in Adipose Tissue: Critical Players in Immunometabolism - Wang, Qun; Wu, Huaizhu (Frontiers in Immunology, 2018)
Adipose tissue performs immunoregulatory functions in addition to fat storage. Various T cells in different fat depots either help maintain metabolic homeostasis under healthy conditions or contribute to metabolic disorders in pathological conditions such as obesity, diabetes, cardiovascular diseases, or even cancer. These T cells play critical roles in immunometabolism, which refers to the intersection of immunity and metabolism. Numerous studies have examined the presence and changes of different T cell subsets, including helper T cells, regulatory T cells, cytotoxic T cells, and natural killer T cells, in adipose depots in health and diseases. In this review, we will discuss the adipose tissue niches that influence the patterns and functions of T cell subsets and in turn the impact of these T cells on cell- or body-based immunometabolism accounting for health and obesity.